Computational modeling and dynamic response of reinforced concrete shear wall under out-of-plane impact loading. (February 2023) - Jin, Liu; Xia, Maoxin; Zhang, Renbo; Lin, Manfang; Du, Xiuli
Highlights: The failure mechanism of RC shear wall under impact loading is analyzed. The impact velocity of drop hammer ranges from 2 m/s to 20 m/s. The effect of edge members on the impact resistance of RC shear wall is explored. The effect of impact velocity on the shape of impact force time history is analyzed. Abstract: The purpose of the present work is to study the impact performance of the reinforced concrete shear wall. Considering the bond-slip and strain rate enhancement effects of steel and concrete, a numerical model for the study of the impact resistance of reinforced concrete shear walls was established. The numerical model was validated by comparing the simulation results with those observed during the drop hammer impact test. Based on the simulation results, the failure mechanism of reinforced concrete shear walls under impact loading was analyzed. The influence of impact velocity and edge members on the impact resistance of reinforced concrete shear walls was revealed. The results show that the dynamic response of the wall changes most obviously from the instant of peak impact force to the peak reaction force. The damage on the rear surface of the wall is more serious than the impact surface. The local damage of reinforced concrete shear walls is more serious for higher impact velocity. The maximum and residual displacement in the middle of the wall shows a quadratic growth relationship with the impact velocity and a linear growth relationship with the impact energy. With the increase in impact velocity, the peak and platform value of impact force first increase linearly, and then does not change remarkably while the duration increases linearly. The peak reverse reaction force varies irregularly with the increase in impact velocity due to the inertia of the wall. The influences of impact velocity and edge members on the value and duration of reaction force are similar to those on the impact force. Under impact loading, both the maximum positive and negative bending moment appear in the area near the impact location. The increase in impact velocity can elevate the internal force while edge members affect the shear force more than the bending moment. The change in impact velocity affects the energy distribution in steel and concrete during impact. Configuration of edge members can effectively enhance the impact resistance of the wall due to the improvement in global stiffness. The mid-span displacement of the wall and the duration of impact force are reduced and the energy dissipation capacity of concrete is improved.